The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3390/biomedicines10020335
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Cells in Multiple Sclerosis: From Blood to Brain

Abstract: Multiple sclerosis (MS) is a chronic, autoimmune, and neurodegenerative disease of the central nervous system (CNS) that affects myelin. The etiology of MS is unclear, although a variety of environmental and genetic factors are thought to increase the risk of developing the disease. Historically, T cells were considered to be the orchestrators of MS pathogenesis, but evidence has since accumulated implicating B lymphocytes and innate immune cells in the inflammation, demyelination, and axonal damage associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 185 publications
(261 reference statements)
0
26
0
3
Order By: Relevance
“…Since myelin-reactive T cells are found in healthy individuals, it was suggested that MS pathogenesis could be associated with insufficient immune regulation by Tregs (176). Tregs could suppress the activity of Th1 and Th17 effector cells (Teff), cytotoxic CD8+ T cells (Tc), and antigen-presenting cells (APCs) by direct contact and secretion of suppressive cytokines (177). By presenting myelin, APCs could trigger activation and differentiation of pathogenic Th1 and Th17 cells, releasing proinflammatory cytokines such as IFN-g, TNF-a and IL-17 (178).…”
Section: Tregsmentioning
confidence: 99%
“…Since myelin-reactive T cells are found in healthy individuals, it was suggested that MS pathogenesis could be associated with insufficient immune regulation by Tregs (176). Tregs could suppress the activity of Th1 and Th17 effector cells (Teff), cytotoxic CD8+ T cells (Tc), and antigen-presenting cells (APCs) by direct contact and secretion of suppressive cytokines (177). By presenting myelin, APCs could trigger activation and differentiation of pathogenic Th1 and Th17 cells, releasing proinflammatory cytokines such as IFN-g, TNF-a and IL-17 (178).…”
Section: Tregsmentioning
confidence: 99%
“…Multiple sclerosis (MS) is an autoimmune and inflammatory disease of the CNS, characterized by the degradation of the myelin sheaths that cover the brain and spinal cord [ 87 ]. The MS etiology has not been fully elucidated, but the main cause is known to be the loss of self-tolerance developed against various CNS antigens and myelin sheaths [ 88 , 89 ].…”
Section: Microbiota–gut–brain Axis (Mgb)mentioning
confidence: 99%
“…The MS etiology has not been fully elucidated, but the main cause is known to be the loss of self-tolerance developed against various CNS antigens and myelin sheaths [88,89].…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…Multiple sclerosis (MS) is a common autoimmune, neurodegenerative disease of the central nervous system (CNS) (Calahorra et al, 2022 ). More than two million people around the world suffer from it, which brings a huge social and economic burden to patients (Browne et al, 2014 ; Kobelt et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%